Crypt dysplasia in Barrett's oesophagus shows clonal identity between crypt and surface cells. Issue 1 (6th August 2013) - Khan, Shabuddin; McDonald, Stuart AC; Wright, Nicholas A; Graham, Trevor A; Odze, Robert D; Rodriguez‐Justo, Manuel; Zeki, Sebastian
Abstract Epithelial dysplasia is an important histological diagnosis signifying the presence of pre‐invasive disease, usually needing intervention. However, the specific genetic changes responsible for the induction of this phenotypic change are unknown. Moreover, recent reports indicate that the dysplastic phenotype may not be immutable: in basal crypt dysplasia (CD), unequivocal dysplastic changes are seen in the crypts in Barrett's oesophagus and other pre‐invasive lesions in the gastrointestinal tract, but the upper crypts and surface epithelium associated with these dysplastic crypts show the definitive morphology of a differentiated epithelium. The genotypic relationship between CD and the differentiated surface epithelium is presently unclear. We obtained 17 examples of CD: the lower and upper crypts and surface epithelium were differentially laser‐microdissected from formalin‐fixed, paraffin‐embedded sections and mutations were sought in tumour suppressor genes frequently associated with progression in Barrett's oesophagus. We found two patients who both showed a c. C238T mutation in the CDKN2A (CDKN2AInk4A) gene and where the precise microanatomical relationships could be discerned: this mutation was present in both the CD at the crypt base and in the upper crypt and surface epithelium. We conclude that, in CD, the dysplastic basal crypt epithelium and the upper crypt and surface epithelium show clonal CDKN2A mutations, thus showing definitively that the surface epithelium is derived from the dysplastic crypt epithelium: the dysplastic phenotype is therefore not fixed and can be reversed. The mechanism of this change is unclear but may be related to the possibility that dysplastic cells can, probably early in their progression, respond to differentiation signals. However, it is also clear that a heavy mutational burden can be borne by crypts in the gastrointestinal tract without the development of phenotypic dysplasia. We are evidently some way from understanding the plasticity and the genotypic correlates of the dysplastic phenotype. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.